G155 Small For Gestational Age at Birth and Lung Function at School Age in Very Prematurely Born Children. (4th June 2013) - Zivanovic, S; Peacock, JL; Lo, J; Lunt, A; Odedra, R; Calvert, S; Marlow, N; Greenough, A
Abstract : Background: Very prematurely born infants who were small for gestation age (SGA) at birth, despite routine use of antenatal corticosteroids and postnatal surfactant, had increased respiratory morbidity in infancy – increased rates of BPD and hospital readmissions for respiratory disorders (1). Aim: To test the hypothesis that amongst children born very prematurely, those who were SGA would have greater lung function abnormalities at school age. Methods: Lung function was assessed at 12 to 13 years of age in 204 children born <29 weeks of gestational age; 50 were SGA (<10th centile for weight). They had been entered into the United Kingdom Oscillation Study and randomised within one hour after birth to receive high frequency oscillation or conventional ventilation. There were no significant differences in short term outcomes (2), hence the results of the children in the two arms were pooled for this study. Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), FEV1:FVC, residual volume (RV), diffusion factor for carbon monoxide (DLCO), functional residual capacity (FRCpleth) and maximum expiratory flow at 24, 50, 75% of vital capacity (MEF25, 50, 75) were assessed. The results were expressed as z-scores. The response to a cold air challenge (CACh) was considered positive if FEV1 fell by >10% of baseline. Results: At the time of assessment, compared to the non SGA children, the SGA children had lower weight (p < 0.001) and height (p = 0.002). The SGA children had lower mean z-scores for FEV1 (p < 0.001), FEV1/FVC (P = 0.009), DLCO (p = 0.013), MEF25 (p = 0.005), MEF50 (p = 0.002) and MEF75 (p < 0.001) and a higher mean FRCpleth z-score (p = 0.010). There was no significant difference regarding the proportion of SGA and non SGA children responding to a CACh (p = 0.091). Conclusion: These results suggest that amongst very prematurely born children, being SGA at birth is associated with greater restrictive and obstructive (particularly of small airways) lung function abnormalities at school age. References: Peacock J, Marston L, Marlow N, et al Neonatal and infant outcome in boys and girls born very prematurely. Ped Res 2012; 71:305–310. Johnson AH, Peacock JL, Greenough A, et al High frequency oscillatory ventilation for the prevention of chronic lung disease of prematurity. New Engl J Med 2002; 347:633–642.